Comparison of Parental Report of Influenza Vaccination to Documented Records in Children Hospitalized With Acute Respiratory Illness, 2015–2016. (12th October 2020) - Ogokeh, Constance E; Campbell, Angela P; Feldstein, Leora R; Weinberg, Geoffrey A; Staat, Mary A; McNeal, Monica M; Selvarangan, Rangaraj; Halasa, Natasha B; Englund, Janet A; Boom, Julie A; Azimi, Parvin H; Szilagyi, Peter G; et al.
Abstract: Background: Parent-reported influenza vaccination history may be valuable clinically and in influenza vaccine effectiveness (VE) studies. Few studies have assessed the validity of parental report among hospitalized children. Methods: Parents of 2597 hospitalized children 6 months–17 years old were interviewed from November 1, 2015 to June 30, 2016, regarding their child's sociodemographic and influenza vaccination history. Parent-reported 2015–2016 influenza vaccination history was compared with documented vaccination records (considered the gold standard for analysis) obtained from medical records, immunization information systems, and providers. Multivariable logistic regression analyses were conducted to determine potential factors associated with discordance between the 2 sources of vaccination history. Using a test-negative design, we estimated VE using vaccination history obtained through parental report and documented records. Results: According to parental report, 1718 (66%) children received the 2015–2016 influenza vaccine, and of those, 1432 (83%) had documentation of vaccine receipt. Percent agreement was 87%, with a sensitivity of 96% (95% confidence interval [CI], 95%–97%) and a specificity of 74% (95% CI, 72%–77%). In the multivariable logistic regression, study site and child's age 5–8 years were significant predictors of discordance. Adjusted VE among children who received ≥1 dose of the 2015–2016 influenza vaccine per parental report was 61% (95% CI, 43%–74%), whereas VE using documented records was 55% (95% CI, 33%–69%). Conclusions: Parental report of influenza vaccination was sensitive but not as specific compared with documented records. However, VE against influenza-associated hospitalizations using either source of vaccination history did not differ substantially. Parental report is valuable for timely influenza VE studies. Abstract : Parental report was reliable and concordant with influenza vaccination history from documented records in hospitalized children with acute respiratory illness at 7 pediatric hospitals. Influenza vaccine effectiveness estimates did not differ substantially using either source of vaccination history.